A “desagregação” do Ensino Superior (The “unbundling” of Higher Education) - McCowan, Tristan (Revista Eletrônica de Educação, 2018)
Abstract Unbundling is the process through which products previously sold together are separated into their constituent parts. In higher education, this dynamic has been driven primarily by financial motivations, and spearheaded by the for-profit sector, but also has pedagogical motivations through its emphasis on personalization and employability. This article presents a theoretical analysis of the trend, proposing new conceptual tools with which to map the normative implications. While appearing to offer the prospect of financial viability and increased relevance, unbundling presents some worrying signs for universities: frst, the removal of possible synergies between teaching and research, and between different modes of learning; second, the undermining of the ability of institutions to promote the public good and ensure equality of opportunity; and third, the threat of hyperporosity to the conducting of basic research with long-term benefits. Keywords: Commodifcation, For-profit higher education, Future of the university, MOOcs. Resumo A desagregação é o processo pelo qual os produtos anteriormente vendidos em conjunto são separados em suas partes constituintes. No ensino superior, esta dinâmica tem sido impulsionada principalmente por motivações financeiras e liderada pelo setor com fins lucrativos, mas também tem motivações pedagógicas através da ênfase na personalização e na empregabilidade. Este artigo apresenta uma análise teórica da tendência, propondo novas ferramentas conceituais para mapear as implicações normativas. Embora pareça oferecer perspectivas de viabilidade financeira e maior relevância, a desagregação apresenta alguns sinais preocupantes para as universidades: primeiro, a remoção de possíveis sinergias entre ensino e pesquisa, e entre diferentes modos de aprendizagem; em segundo lugar, o enfraquecimento da capacidade das instituições de promover o bem público e garantir a igualdade de oportunidades; e, em terceiro lugar, a ameaça de hiperporosidade na realização de pesquisas básicas com benefícios no longo prazo. Palavras-chave: Comoditização, Ensino Superior com fins lucrativos, Futuro da universidade, MOOCs. References AGARWAL, A. Unbundled: Reimagining Higher Education. The Huffington Post, 9 December, 2013. Disponível em: http://www.huffingtonpost.com/anant-agarwal/unbundled-reimagining-higher-education_b_4414048.html, acesso em 9/2/17. ANDERSON, R. British Universities Past and Present. London: Continuum, 2006. BARBER, M.; DONNELLY, K.; RIZVI, S. An avalanche is coming. London, UK: Institute for Public Policy Research, 2013. Disponível em: http://www.ippr.org/files/images/media/files/publication/2013/04/avalanche-is-coming_Mar2013_10432.pdf?noredirect=1 acesso em 9/2/17. BIGGS, J. What the Student Does: teaching for enhanced learning. Higher Education Research & Development, 18 (1), 57-75, 1999. BOK, D. Universities in the Marketplace: the commercialization of higher education. Princeton: Princeton University Press, 2003. BONI, A.; LOPEZ-FOGUES, A.; WALKER, M. Higher education and the post 2015 agenda. A contribution from the human development approach. Journal of Global Ethics, 12 (1), 17-28, 2016. BOWEN, W. G. Higher education in the digital age. Princeton: Princeton University Press, 2013. CHRISTENSEN, C. M.; HORN, M. B.; CALDERA, L.; SOARES, L. Disrupting college: How disruptive innovation can deliver quality and affordability to postsecondary education. The Center for American Progress. 2011. Recuperado de: http://www.americanprogress.org/issues/2011/02/disrupting_college.html, 9/2/17 COLEMAN, J. S. The idea of the developmental university, Minerva: A review of Science, Learning and Policy, 24(4), 476–494, 1986. COLLINI, S. What are universities for? London: Penguin, 2012. COWEN, R. Robustly Researching the Relevant: A Note on Creation Myths in Comparative Education. In: WIKANDER, L.; GUSTAFFSON, C.; RIIS, U. (eds.) Enlightenment, Creativity and Education: Polities, Politics, Performances, pp. 3–26. Rotterdam: Sense Publishers & CESE, 2012. CRAIG, R. College disrupted: The great unbundling of higher education. New York, NY: Palgrave Macmillan, 2015. de JONGHE, A. Reorganising the teaching-research tension. Higher Education Management and Policy, 17(2), 61–76, 2005. de RIDDER-SYMOENS, H. (ed.) A History of the University in Europe (Volume 2). Universities in Early Modern Europe (1500-1800). Cambridge: Cambridge University Press, 1996. DIANATI, S. What do Massive Open Online Courses (MOOCs) Have To Do With ‘Good’ Education?: An Ideology Critique of MOOCs. Unpublished PhD thesis. Flinders University, 2016. GEHRKE, S.; KEZAR, A. Unbundling the faculty role in higher education: Utilizing historical, theoretical, and empirical frameworks to inform future research. In: Higher Education: Handbook of Theory and Research (pp. 93-150). Springer International Publishing, 2015. GIBBONS, M.; LIMOGES, C.; NOWOTNY, H.; SCHWARTZMAN, S.; SCOTT, P.; TROW, M. The new production of knowledge: The dynamics of science and research in contemporary societies. London: SAGE Publications Ltd., 1994. GROVE, J. Troubling FX as Falmouth forces staff to go private. Times Higher Education, 3rd January, 2013. HATTIE, J.; MARSH, H.W. The relationship between research and teaching—a meta-analysis. Review of Educational Research 66: 507–542, 1996. HERK, M. Fixing Our Broken Colleges: Competency-Based Education and Reauthorizing the Higher Education Act. Committee for Economic Development. 2015. Disponível em: https://www.ced.org/blog/entry/fixing-our-broken-colleges-competency-based-education-and-reauthorizing-the , acesso em 9/2/17. HORN, M. Unbundling and Re-bundling In Higher Education. Forbes, 10 July, 2014. Disponível em: http://www.forbes.com/sites/michaelhorn/2014/07/10/unbundling-and-re-bundling-in-higher-education/#7ebaea2e79c2 , acesso em 7/9/17. ILLICH, I. Tools for conviviality. New York: Harper & Row, 1973. INEP. Censo da Educação Superior 2016. Notas estatísticas. Brasília: INEP, 2017. KEPLER. Kepler: Higher education for all. 2016. http://www.kepler.org/. Acesso em 7/6/2016. KERR, C. The Uses of the University. New York: Harper Torchbooks, 1963. KINSER, K. Working at for-profit universities: The University of Phoenix as a new model. International Higher Education, (28), 13-14, 2002. LITAN, R. E. The case for ‘unbundling’ higher education. Brookings Institute, 2015. Disponível em: https://www.brookings.edu/articles/the-case-for-unbundling-higher-education/, acesso em 9/2/17 MACFARLANE, B. The Academic Citizen: the Virtue of Service in University Life. London: Routledge, 2007. MACFARLANE, B. The morphing of academic practice: Unbundling and the rise of the para-academic. Higher Education Quarterly, 65(1), 59–73, 2011. MARGINSON, S. Higher education and public good. Higher Education Quarterly, 65(4), 411–433, 2011. MARGINSON, S. What holds the conglomerate university together? Paper presented at the Education, Practice and Society seminar, UCL Institute of Education, London, 16 November, 2016a. MARGINSON, S. The dream is over: The Crisis of Clark Kerr’s Californian Idea of Higher Education. Berkeley: University of California Press, 2016b. McCOWAN, T. The growth of private higher education in Brazil: Implications for equity and quality. Journal of Education Policy, 19, 453–472, 2004. McCOWAN, T. Should universities promote employability? Theory and Research in Education. 13 (3), 267-285, 2015. McCOWAN, T. Universities and the post-2015 development agenda: an analytical framework. Higher Education 72 (4), 505-523, 2016a. McCOWAN, T. Three dimensions of equity of access in higher education. Compare: a Journal of Comparative and International Education. 46 (4), 645-665, 2016b. PAULSON, K. Recon?guring faculty roles for virtual settings. Journal of Higher Education, 73(1), 123–140, 2002. ROBERTSON, S. L.; KOMLJENOVIC, J. Non-state actors, and the advance of frontier higher education markets in the global south. Oxford Review of Education, 42 (5), 2016a. ROBERTSON, S. L; KOMLJENOVIC, J. Unbundling the University and Making Higher Education Markets. In: VERGER, A.; LUBIENSKI, C.; STEINER-KAMSI G. (Eds.), World Yearbook in Education (Global edu). London: Routledge, 2016b. SCHWARTZMAN, S. Equity, Quality and Relevance in Higher Education in Brazil. Anais da Academia Brasileira de Ciências, 76 (1), 2004. SELINGO, J. J. College unbound: The future of higher education and what it means for students. Boston: New Harvest, 2013. TOMLINSON, M. Graduate employability: A review of conceptual and empirical themes. Higher Education Policy 25: 407–431, 2012. TROUTT, W. E. Unbundling instruction: Opportunity for community colleges. Peabody Journal of Education, 56(4), 253-259, 1979. UIS (UNESCO Institute for Statistics) Statistical Tables. Education: Gross Enrolment Ratio by Level of Education. 2017. http://data.uis.unesco.org/?queryid=142 Acesso em 15/12/2016. UNIVERSITYNOW. Why we’re different. Making higher education affordable. 2017. Disponível em: http://unow.com/making-education-affordable/ , acesso em 9/2/17. VASAGAR, J. No frills university college offers half price degrees. The Guardian, 11 October, 2011. Disponível em: https://www.theguardian.com/education/2011/oct/17/coventry-university-college-half-price-degree , acesso em 9/2/17. WANG, W. K. S. The unbundling of higher education. Duke Law Journal, 1, 53-90, 1975. WILDAVSKY, B. Evolving toward signi?cance or MOOC ado about nothing. International Educator, May/June, 74–79, 2014.